THE EFFECT OF QUIZIZZ MEDIA IN IPS LEARNING MATERIALS OF THE ARRIVAL OF WEST NATIONS TO INDONESIA ON LEARNING OUTCOMES AND STUDENTS' LEARNING MOTIVATION - Ananda, Prasela Nur (Program Studi S1 Pendidikan IPS, Universitas Negeri Surabaya, 2022)
The COVID-19 epidemic has had an influence on the educational sector, necessitating the use of the internet for teaching and learning. Because learning media have an impact on motivation for learning, there is a need for innovations made by teachers during the teaching process that can inspire students to be enthusiastic learners. The goal of this study was to examine how learning results and student motivation at SMP Negeri 27 Surabaya were affected by Quiziz media in social studies learning material on the introduction of western nations in Indonesia. This study usesa Pre-Experimental Design by using two classes, namely the control class and the experimental class. The control class value was obtained from the learning value without using quizzz media while the experimental class was given treatment in the form of quizizz media. The sample consists of 2 classes,namely class VIII H as the experimental class and VIII-A as the control class, using only posttest. Where obtained from the research results that the value of sig. from Levene's test of 0.633 which indicates that the data comes from the same variance. Results sig. (2-tailed) Equal variances assumedof 0.004 < 0.05. So the conclusion obtained is that the quizizz media has a significant influence on student learning outcomes at SMP Negeri 27 Surabaya. The results of the questionnaire on learning motivation in the experimental class were 2.7% with one student